Safening activity and metabolism of the safener cyprosulfamide in maize and wheat. Issue 10 (10th March 2020) - Giannakopoulos, George; Dittgen, Jan; Schulte, Wolfgang; Zoellner, Peter; Helmke, Hendrik; Lagojda, Andreas; Edwards, Robert
Abstract: BACKGROUND: Safeners extend the application of existing herbicides by selectively enhancing tolerance in large‐grained cereal crops. While their activity is linked to enhanced herbicide metabolism, their exact mode of action and reasons for their crop specificity have yet to be determined. In this study, we investigated the selectivity of the recently developed sulfonamide safener cyprosulfamide (CSA) in maize ( Zea mays L. ) and wheat ( Triticum aestivum ), focusing on its uptake, distribution and metabolism in the two species. RESULTS: CSA protected maize, but not wheat, from injury by thiencarbazone‐methyl (TCM). This correlated with the selective enhanced detoxification of the herbicide in maize. CSA underwent more rapid metabolism in maize than in wheat, with the formation of a specific hydroxylated metabolite correlating with safening. Studies with the nsf1 mutant sweetcorn line showed that the hydroxylation of CSA was partly mediated by the cytochrome P450 CYP81A9. However, primary metabolites of CSA were chemically synthesised and tested for their ability to safen TCM in maize but when tested were inactive as safeners. CONCLUSION: The results of this study suggest that the protection against TCM injury by CSA is linked to enhanced herbicide metabolism. This selective activity is due to the specific recognition of parent CSA in maize but not in wheat. Subsequent rapid oxidative metabolism of CSA led to its inactivation, demonstrating that cytochrome P450s regulate the activity of safeners as well as herbicides. © 2020 Society of Chemical Industry Abstract : Cyprosulfamide enhances the detoxification of TCM in maize but not in wheat and this was associated with the enhanced oxidative metabolism of the safener by cytochromes P450 (CYPs), including CYP81A9. © 2020 Society of Chemical Industry